Prototype of Nitro Compound Vapor and Trace Detector Based on a Capacitive MIS Sensor - Nikolay Samotaev; Artur Litvinov; Maya Etrekova; Konstantin Oblov; Dmitrii Filipchuk; Alexey Mikhailov (Sensors, 2020)
A prototype of a nitro compound vapor and trace detector, which uses the pyrolysis method and a capacitive gas sensor based on the metal−insulator−semiconductor (MIS) structure type Pd−SiO2−Si, was developed and manufactured. It was experimentally established that the detection limit of trinitrotoluene trace for the detector prototype is 1 × 10−9 g, which corresponds to concentration from 10−11 g/cm3 to 10−12 g/cm3. The prototype had a response time of no more than 30 s. The possibility of further improving the characteristics of the prototype detector by reducing the overall dimensions and increasing the sensitivity of the MIS sensors is shown.